2018
DOI: 10.3390/en11020376
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lignin Chemistry of Switchgrass due to Delignification by Sodium Hydroxide Pretreatment

Abstract: Switchgrass was pretreated with sodium hydroxide (NaOH) at various concentrations and pretreatment times to investigate how delignification caused by NaOH affects its lignin chemistry. NaOH resulted in significant delignification ranging from 44.0 to 84.6% depending on pretreatment intensity. While there was no significant glucan loss due to NaOH pretreatment, higher NaOH concentrations removed xylan by up to 28.3%. Nitrobenzene oxidation (NBO) was used to study changes in lignin chemistry, and indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…Angiosperm hardwood lignin, such as that of poplar, is made of approximately 60% sinapyl alcohol (S-type lignin) and 40% coniferyl alcohol . In addition to S- and G-type lignins, wild-type grasses can contain 20–50% lignin as p -coumaryl alcohol units (H-type lignin). , The S/G/H lignin ratio of bioenergy crops can now be genetically tuned, and modified lignin strains often require lower pretreatment severities for cellulose separation and subsequent conversion to fermentable sugars. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiosperm hardwood lignin, such as that of poplar, is made of approximately 60% sinapyl alcohol (S-type lignin) and 40% coniferyl alcohol . In addition to S- and G-type lignins, wild-type grasses can contain 20–50% lignin as p -coumaryl alcohol units (H-type lignin). , The S/G/H lignin ratio of bioenergy crops can now be genetically tuned, and modified lignin strains often require lower pretreatment severities for cellulose separation and subsequent conversion to fermentable sugars. , …”
Section: Introductionmentioning
confidence: 99%
“…5 In addition to S-and G-type lignins, wildtype grasses can contain 20−50% lignin as p-coumaryl alcohol units (H-type lignin). 6,7 The S/G/H lignin ratio of bioenergy crops can now be genetically tuned, and modified lignin strains often require lower pretreatment severities for cellulose separation and subsequent conversion to fermentable sugars. 8,9 Because of lignin's potential to provide diverse and versatile feedstocks for materials science 10 and organic synthesis, 11 chemical and biological lignin depolymerization have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the concentration of KOH was increased (30 wt % of lignin) based on total lignin content. The higher alkali concentration in the solution facilitated the depolymerization of the lignin units. , All experimental conditions and other properties and characterizations can be found in Table S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, NaOH treatments may be employed after enzymatic hydrolysis for lignin extraction and recovery for lignin utilization in co-products applications. , One advantage of utilizing NaOH extraction and solubilization of lignin is that lignin-formaldehyde resins are ultimately formulated under alkaline conditions and potentially this approach could remove a lignin precipitation/recovery step. As a potential disadvantage of NaOH lignin extraction, previous studies have shown that NaOH treatment of lignin results in the reduction of phenolic hydroxyl content especially the reduction of p -hydroxyphenyl subunits, presumably due to the alkali-catalyzed hydrolysis esters of p CA pendant groups on lignin . Notably, our prior work utilized NaOH extraction to isolate lignin from polysaccharide-rich residues such as lignin cake .…”
Section: Resultsmentioning
confidence: 99%